Government healthcare spending in times of economic sanctions - Salem Al Mustanyir (Global Security: Health, Science and Policy, 2024)
Worldwide, countries are constantly exposed to the effects of global political and economic changes owing to benefit-sharing connections, whereby changes in the forms of relationships and sanction impositions can put pressure on countries’ financing systems, including the healthcare sector. This study examines the effects of economic sanctions on government healthcare spending. Quantitative data on government healthcare spending from the WHO covering the 2000–2020 period were evaluated using the Wilcoxon – Mann – Whitney test. The results showed that government healthcare spending in Iraq, Libya, and Iran did not respond to economic sanctions but it did decline significantly in Venezuela, suggesting a limited effect on countries with long economic sanction experiences. With the world’s continuous political and economic uncertainty, countries worldwide should not focus on short-term plans but regularly revise and bolster their healthcare financing pool and maintain financing strategies that limit the effect of global political and economic changes.